2017
DOI: 10.1002/path.4919
|View full text |Cite
|
Sign up to set email alerts
|

WWC3 regulates the Wnt and Hippo pathways via Dishevelled proteins and large tumour suppressor 1, to suppress lung cancer invasion and metastasis

Abstract: The scaffolding protein WWC (WW and C2-domain containing) family is known to regulate cell proliferation and organ size via the Hippo signalling pathway. However, the expression level of WWC3 in human tumours and the mechanisms underlying its role in cellular signal transduction have not yet been reported. Herein, we explored the potential roles of WWC3 in lung cancer cells and the corresponding molecular mechanisms. We found low WWC3 expression in both lung cancer cell lines and lung cancer specimens, which w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
67
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 62 publications
(72 citation statements)
references
References 27 publications
5
67
0
Order By: Relevance
“…Wnt/β‐catenin signaling pathway has been reported to play a crucial role in multiple aspects of tumor progression, including NSCLC (Han et al, ; Seto et al, ; Tang et al, ). In addition, it has been known that Wnt/β‐catenin signaling pathway is involved in cancer invasion and metastasis (Farahmand, Darvishi, Majidzadeh‐A, & Ansari, ; Rong, Zhao, & Lu, ).…”
Section: Introductionmentioning
confidence: 99%
“…Wnt/β‐catenin signaling pathway has been reported to play a crucial role in multiple aspects of tumor progression, including NSCLC (Han et al, ; Seto et al, ; Tang et al, ). In addition, it has been known that Wnt/β‐catenin signaling pathway is involved in cancer invasion and metastasis (Farahmand, Darvishi, Majidzadeh‐A, & Ansari, ; Rong, Zhao, & Lu, ).…”
Section: Introductionmentioning
confidence: 99%
“…Wnt‐Hippo crosstalk has been well established among tumor cells . These two pathways are closely related to apoptosis, proliferation, invasion, and metastasis.…”
Section: Resultsmentioning
confidence: 99%
“…Beyond this "cell density" aspect both pathways may also coordinate in managing the immune phenotype and apoptosis of cancer cells (10,11). Han et al (2) have expanded our knowledge and have shown that an upstream component of Hippo signaling, WWC3, not only inhibits YAP1, it also inhibits beta-catenin accumulation in the nucleus.…”
Section: Cell-cell Adhesionmentioning
confidence: 99%
“…However, this causes WWC3 or WWC family members to become weak spots in the anti-tumor defense system. Han et al showed that WWC3 expression is down-regulated during lung cancer progression and its expression may become a novel marker for poor prognosis of non-small cell lung cancer (2). WWCs are highly similar and they all have the ability to regulate LATS1/2 protein function.…”
Section: Cell-cell Adhesionmentioning
confidence: 99%
See 1 more Smart Citation